The composition of phenolic compounds in Chinese olive (Canarium album L.) cultivars and their contribution to the anti-inflammatory properties of the cultivars - He, Fangqing; Du, Yixuan; Pan, Zhuangguang; Zeng, Huize; Luo, Haolin; Wang, Junyi; Sun, Yuanming; Li, Meiying (Frontiers in Nutrition, 2024)
This study aimed to explore the phenolic compounds (PCs) present in three Chinese olive (Canarium album L.) cultivars and the contribution of these PCs to the antiinflammatory activities of the cultivars.Ultra-high performance liquid chromatography coupled with hybrid quadrupoleorbitrap/mass spectrometry (UPLC-Q-Exactive/MS) was used to identify and quantify the PCs present in three Chinese olive cultivars, "Na zhong", "Tan xiang", and "Xiang zhong". 2,2-diphenyl-1-picrylhydrazyl (DPPH); 2,2′-azinobis (3-ethylbenzothiazoline 6-sulfonate) (ABTS); and oxygen radical absorption capacity (ORAC) assays were used to assess the antioxidant activities of the PCs. Furthermore, we analyzed the antiinflammatory action of these PCs using lipopolysaccharide (LPS)-induced RAW264.7 cells.A total of 44 PCs were identified in the three cultivars. Of these, 17 PCs were previously unidentified in Chinese olive. Among the cultivars, the free phenolics (FPs) of "Tan xiang" showed the strongest antioxidant activity. All cultivars have shown significant inhibition of TNF-α and IL-6 production. Clustering correlation analysis showed galloyl-bis-HHDP-glucose and paeonol have significant antiinflammatory ability in FPs. Quininic, galloylquinic acid, 4-hydroxycinnamic acid and gallic acid hexoside have shown significant inhibition of IL-6 production in BPs.Furthermore, gallic acid, catechin, syringic acid, and nobiletin exhibit negative correlation in FPs and positive correlation in BPs of cytokine production, while corilagin and methyl ellagic acid pentoside exhibited opposite correlation.In summary, this study contributed to the literature on PCs in Chinese olives and the potential health benefits of FPs and BPs.